Índices climáticos e infestação predial por larvas de Aedes aegypti (Linnaeus, 1762) e Aedes albopictus (Skuse, 1894) em Araçatuba-sp Brasil - Lima, Luiz Gustavo Ferraz; Silva, Elba Camila Peccin; Rodrigues, Tamiris Eugênio; Perri, Sílvia Helena Venturoli [UNESP]; Rodas, Lilian Aparecida Colebrusco; Freitas, Neusa Madalena Bertani de (My University, 2013)
Aedes is synanthropic; associated with climatic conditions and urban environment. This study performed a retrospective evaluation of the climatic indices and the A. aeypti and A. albopictus infestation larvae rates (IP), registered from the month of October, 2005 to 2009, in the Araçatuba city, São Paulo State. There was no variation in the average temperature in the period (26.3°C). The rain falls were high in 2005 (133.5 mm3 ) fell in 2006, 2007 and 2008 (55.0 mm3 , 78.5 mm3 and 79.0 mm3 , respectively) and increased in 2009 (104.0 mm3 ). The infestation IP was 1.10, 1.39, 0.36, 0.28 and 3.30, respectively in 2005, 2006, 2007, 2008 and 2009, none of them were A. albopictus larvae. There was no association between IP and temperature, but there was significant difference (P <0.001) between the IP of 2009, with the IP of 2007 and 2008. This study it was concluded that among the environmental factors just rain influenced the rate of larvae, "infestation", committed only by A. aegypti.

Aedes é sinantrópico; está associado às condições climáticas e do ambiente urbano. O presente estudo realizou uma avaliação retrospectiva dos índices climáticos e dos índices de infestação predial (IP), de larvas dos vetores A. aeypti e A. albopictus, referentes ao mês de outubro de 2005 a 2009, no município de AraçatubaSP. Os resultados não demonstraram variação significativa da temperatura, comparada à média dos cinco anos (26,3°C). As chuvas foram maiores em 2005 (133,5mm), diminuiu em 2006, 2007 e 2008 (55,0 mm, 78,5 mm, e 79,0 mm) e aumentou em 2009 (104,0mm). A Infestação Predial foi 1,10; 1,39; 0,36; 0,28 e 3,30 respectivamente em 2005, 2006, 2007, 2008 e 2009, nenhuma delas causada por A. albopictus. Não foi observada associação entre IP e temperatura, contudo houve diferença significativa (P<0,001) entre o IP de 2009 com os IP de 2007 e 2008. Por meio desse estudo pode-se concluir que durante no mês de outubro dos cinco anos, a chuva foi o único fator climático que influenciou na variação dos índices de infestação predial, cometida unicamente por A. aegypti. Contudo, provavelmente outros fatores ambientais estão associados aos resultados observados.
Climate indices and infestation by larvae of aedes aegypti (Linnaeus, 1762) and aedes albopictus (Skuse, 1894) in Araçatuba city - Brazil
Keywords: Aedes aegypti; A. albopictus; Dengue; Climate conditions; Aedes aegypt.; A. albopictus; Dengue; Condições climáticas